Advocacy in the context of the COVID-19 pandemic: in defense of the rights to health (Research, Society and Development, 2020)
Objective: To reflect about the applicability of theoretical constructs of advocacy in nursing care, considering the context of the COVID-19 pandemic. Method: Reflective theoretical study performed in the months of May and June 2020, based on national and international scientific literature. We used two theoretical sections for analysis: i) Nursing Work aligned with the principle of human dignity; ii) Fighting the COVID-19 pandemic supported by advocacy and nursing performance. Results: It introduces the principles of human dignity and the right to health; the nursing work performance in the context of the COVID-19 pandemic; the advocacy for nursing and the challenges and strategies for ensuring the right to health of patients/users and nursing workers in the context of the COVID-19 pandemic in Brazil. Conclusion: In order to ensure fundamental rights in the context of the COVID-19 pandemic, the evocation of constitutional principles and advocacy should be highlighted; and, in this context, the nursing professional has an essential role, since he/she can engage in the defense of his/her own health as a worker and citizen, but also in the defense of the health of the patients/users under his/her care, their families and the community at large.